1993
DOI: 10.1084/jem.178.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of T lymphocytes to the site of disease: intrahepatic CD4+ T cells specific for the protein NS4 of hepatitis C virus in patients with chronic hepatitis C.

Abstract: SllmmRryThe adult liver is an organ without constitutive lymphoid components. Therefore, any intrahepatic T cell found in chronic hepatitis should have migrated to the liver after infection and inflammation. Because of the little information available on the differences between intrahepatic and peripheral T cells, we used recombinant proteins of the hepatitis C virus (HCV) to establish specific T cell lines and clones from liver biopsies of patients with chronic hepatitis C and compared them with those present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
117
2
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 31 publications
13
117
2
5
Order By: Relevance
“…In line with other reports (Minutello et al 1993, Sakai et al 1999, Exley et al 2002, our results demonstrate the compartmentalised nature of the immune response to HCV. The correlation between periportal activity and portal CD4 + , as seen in a preliminary study (Viso et al …”
Section: Discussionsupporting
confidence: 82%
“…In line with other reports (Minutello et al 1993, Sakai et al 1999, Exley et al 2002, our results demonstrate the compartmentalised nature of the immune response to HCV. The correlation between periportal activity and portal CD4 + , as seen in a preliminary study (Viso et al …”
Section: Discussionsupporting
confidence: 82%
“…This concept of "original antigenic sin" has been shown to occur after sequential infection of mice with two similar strains of lymphocytic choriomeningitis virus, but has not been demonstrated in evolution from acute to chronic infection. 48 Anti-HCV immune responses may also be compartmentalized to the liver, as some studies suggest, [49][50][51] although others have found that specificities in the 2 compartments are similar, and studies of intrahepatic lymphocyte responses during acute human HCV infection are lacking. Recent evidence suggests that CD4ϩ T cell help is required for efficient development of effector and memory CD8 T cell populations in HIV infection, 52 and when lacking may facilitate viral escape mutation in HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that HCV-specific T lymphocytes could be detected among liver-infiltrating lymphocytes. CD4* T cells specific for the NS4 protein of HCV were derived from the liver tissue of patients with chronic hepatitis C, and appeared to compartmentalize at the site of disease [18]. In addition.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic hepatitis C, HCV-specific T lymphocytes have been found in the peripheral blood, and HCV cytotoxic T cell response has been found to be MHC class I-restricted [15.16]. In addition, several studies have shown that HCV-specific T lymphocytes are present among liver-derived lymphocytes [17,18], thereby emphasizing that T cell response may be a main counterpart of the itnniune response to HCV infection.…”
Section: Introductionmentioning
confidence: 99%